Performance of reinforced concrete slab with opening strengthened using CFRP - Aman, S.S. (MDPI Multidisciplinary Digital Publishing Institute, 2020)
Openings in reinforced concrete (RC) slabs are not commonly prescribed in design codes. Even when they are, they raise concerns regards to the size of the openings and the location of the applied loads. Lack of sufficient information about the load-carrying capacity of the slabs with openings and performance is another concern. Hence, this research addresses the structural behavior of slabs with openings coated with Carbon Fiber Reinforced Polymer (CFRP) sheet. In the experimental part, ten slabs were cast with a dimension of 1000 mm x 530 mm x 25 mm, among which nine slabs had openings and one slab was without opening (control slab). The configuration of the CFRP sheet includes coating in the form of single, double, and triple layers. Experimental results show that the slab with a triple coating of the CFRP layer offers the maximum resistance towards the loading rate. Moreover, with the increase in CFRP layers, the value of deflection is minimized. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.